Neurological manifestations of Chikungunya and Zika infections - Pinheiro, Talys J.; Guimarães, Luis F.; Silva, Marcus Tulius T.; Soares, Cristiane N. (Arquivos de Neuro-Psiquiatria, 2016)
The epidemics of Chikungunya virus (CHIKV) and Zika virus (ZIKV) infections have been considered the most important epidemiological occurrences in the Americas. The clinical picture of CHIKV infection is characterized by high fever, exanthema, myalgia, headaches, and arthralgia. Besides the typical clinical picture of CHIKV, atypical manifestations of neurological complications have been reported: meningo-encephalitis, meningoencephalo-myeloradiculitis, myeloradiculitis, myelitis, myeloneuropathy, Guillain-Barré syndrome and others. The diagnosis is based on clinical, epidemiological, and laboratory criteria. The most common symptoms of ZIKV infection are skin rash (mostly maculopapular), fever, arthralgia, myalgia, headache, and conjunctivitis. Some epidemics that have recently occurred in French Polynesia and Brazil, reported the most severe conditions, with involvement of the nervous system (Guillain-Barré syndrome, transverse myelitis, microcephaly and meningitis). The treatment for ZIKV and CHIKV infections are symptomatic and the management for neurological complications depends on the type of affliction. Intravenous immunoglobulin, plasmapheresis, and corticosteroid pulse therapy are options.
Keywords: Guillain-Barre syndrome; Zika virus; Chikungunya virus